THE ROLE OF AGRICULTURAL INFORMATION ON THE PRODUCTIVITY OF ARABICA COFFEE FARMERS (Case: Sait Buttu Saribu Village, Pematang Sidamanik District, Simalungun Regency) - Septi Wardanti (Institute of Computer Science (IOCS), 2020)
The purposes of this study is to determine the role of agricultural counselor on the productivity of Arabica coffee farmers and to find out the obstacles faced by agricultural counselors in providing information concerning the productivity of Arabica coffee farmers in Sait Buttu Saribu Village, Pematang Sidamanik District, Kabupaten Simalungun. The research location chosen deliberately with two considerations, where the Desa Sait Buttu Saribu is one of the centers for Arabica coffee production and counselor activities. The method of determining the sample in this study used simple random sampling with the research sample were farmers who participated in counseling activities. Data analysis was carried out by means of Likert scale and descriptive analysis. The results showed that the role of agricultural counselor workers as dynamists and facilitators was in the category of important role, while the role of counselor workers as motivators was in the category of very important role and the constraints faced by agriculture counselor in extension activities were that farmers did not participate in counseling activities and there are inadequate facilities and infrastructure.